Implementation of Benson Relaxation Intervention to Reduce Pain in Post Sectio Caesarea Patients - Roslianti, Elis; Utami, Lestari (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Acute pain is a physiological problem found in patients undergoing surgery, one of which is sectio caesarea. Efforts are made to overcome this problem by applying the Benson relaxation technique. Objective: This case study seeks to provide a detailed description of the benson relaxation intervention and its effectiveness in reducing pain in patients undergoing sectio caesarea surgery. Method: The method used is descriptive qualitative, using case study techniques to review nursing care, with reference to the SDKI and SIKI books. The focus of this case study is on an individual, Mrs. N, a 28-year-old woman who underwent sectio caesarea, diagnosed with severe pain and received treatment at Teratai 2 Room of Banjar City Hospital. The case study was conducted from May 30 to June 01, 2024 using data collection strategies of interview, observation, physical examination and documentation study. Result: After providing nursing care to clients who underwent sectio caesarea, the symptoms found at the time of assessment included surgical scar pain precisely in the lower abdomen. The nursing problem found is acute pain associated with physical injury agents, as mentioned in the SDKI book. Appropriate interventions to relieve the pain by doing benson relaxation. When the intervention takes place, the process runs smoothly until the assessment stage. At the evaluation stage there was a decrease in the pain scale from 6 to 3 (0-10). Conclusion: The implementation of benson relaxation proved to be very helpful in reducing post sectio caesarea pain, as evidenced by the client's subjective recognition. This finding is consistent with previous writing, making it a valuable reference for further writing. Benson relaxation intervention can be an alternative way to reduce postoperative pain, one of which is in the case of post sectio caesarea pain experienced in hospitals and health centers.